Quadrotor Control System with Hand Movement Sign as an Alternative Remote Control - Nur Achmad Sulistyo Putro; Andi Dharmawan; Tri Kuntoro Priyambodo (Institute of Advanced Engineering and Science, 2017)
Quadrotor is an unmanned aerial vehicle which is controlled by remote control. Unfortunately, not all of the remote control are easy to use, especially for people who have lacking abilities in piloting. This study aims to design a prototype system to control quadrotor using hand movements, as an alternative to the conventional remote control that more simple. This system is consists of 2 parts, quadrotor and handheld. Both systems can communicate wirelessly using radio frequency 2.4 GHz. The handheld system will read the orientation angle of the hand by IMU sensor and it will be converted into a command to determine the direction motion of the quadrotor. To get the orientation angle from the IMU sensor data, we used DCM sensor fusion method. Quadrotor needs a control system that can make its respond runs optimally. In this study, the method of the control system that used is PID controller. The PID gain obtained using Ziegler-Nichols oscillation method and then fixed again by fine-tuned method.